Circumferential pulmonary vein isolation with second-generation multipolar catheter in patients with paroxysmal or persistent atrial fibrillation: Procedural and one-year follow-up results. (15th August 2017) - Spitzer, Stefan G.; Leitz, Patrick; Langbein, Anke; Karolyi, Laszlo; Scharfe, Frank; Weinmann, Thomas; Rämmler, Carola; Pott, Christian; Mönnig, Gerold; Eckardt, Lars
Abstract: Background: There is a lack of procedural and follow-up data on pulmonary vein isolation (PVI) with the second-generation pulmonary vein ablation catheter® (PVAC Gold) in patients with atrial fibrillation (AF). This study provides data on PVI procedures and 1-year follow-up results with PVAC Gold in patients with AF treated in clinical practice. Methods and results: Three hundred and eighty four patients with documented symptomatic paroxysmal (n = 198) or persistent (n = 186) AF were included in a non-randomized prospectively designed database. Patients were enrolled consecutively at 2 high-volume centers. Procedural as well as 1 year follow-up data were systematically analyzed. Average procedure times ± standard deviations were 94 ± 23 min and 97 ± 23 min, respectively, in patients with paroxysmal and persistent AF. Average fluoroscopy times were 14.7 ± 5.4 min and 15.2 ± 5.6 min and total application times 18.1 ± 5.0 min and 18.8 ± 5.2 min, respectively, in the 2 patient cohorts. At 12 months, 70.7% (70/99) and 61.9% (70/113) of patients with paroxysmal and persistent AF, respectively, were free from AF. Four early complications occurred. In the group with persistent AF, 1 posterior cerebral infarction occurred 2 days after the procedure during initiation of anticoagulation. There was no phrenic nerve palsy or esophageal injury associated with the procedures. No thromboembolic events were recorded during follow-up. Conclusions: In patients with paroxysmal or persistent AF, second generation multi-electrode-phased radiofrequency ablation delivers favorable mid-term PVI success rates with few procedure-related or follow-up complications.